Tree traversal algorithms for real time sound propagation calculation - Charalampous, Panagiotis; Michael-Grigoriou, Despina (My University, 2014)
A major category of algorithms for simulating sound propagation in three dimensional environments is the category of geometrical acoustics which are based on various tracing techniques. All tracing techniques are essentially tree traversals throughout a tree of candidate sound paths which could potentially affect the sound field at a given receiver location. Even though there is significant literature for speeding up tracing in three dimensional spaces for use in real time applications, the type of these algorithms has barely been discussed. In this work, we implement an image source method variant and we compare three different tree traversal approaches, depth-first, breadth-first and best-first. We examine their performance in respect to time and we highlight the advantages and disadvantages of each one and evaluate the applicability of each in real time sound propagation calculations.
Keywords: Algorithms; Acoustic fields; Acoustic wave propagation; Acoustics